Chapter 5 Beyond dichotomous gender stereotyping An analysis of global news coverage of Jacinda Ardern's leadership - Żukiewicz, Przemysław (Taylor & Francis, 2022)
Gender, Politics, Elections, Democracy, LGBTQ